Contexto de empreeendimentos eólicos na bahia sob perspectivas de diferentes players - OLIVEIRA, Paulo Vitor Branquinho de (2016)
The Brazilian electricity sector has been significantly affected in its energy supply capacity, due to the dependence on hydroelectric generation, as the great source to supply the energy needs, thus leaving it hostage to the rainfall of its reservoirs. In addition, nowadays, great difficulties are imposed, either environmental, social or political, so that the constructions of new hydroelectric is feasible, either with accumulation reservoirs or by water, which have always been the basis of the Brazilian electrical matrix. This work seeks to demonstrate through several analyzes that wind energy, which is having a strong growth in Bahia, has a great potential diagnosed in its Wind Atlas of 2013, and can be used as complementary energy fo r the state hydroelectric power plants. The use of wind energy may bring to the electric sector of Bahia an operating condition, which minimizes possible generation difficulties or energy deficits, thus guaranteeing a reliable supply of energy in the State. In this way, the work presents a detailed evaluation in the search for solutions to the obstacles and bottlenecks for the expansion of wind power generation in Bahia, under the perspective of entrepreneurs in the wind industry chain with the perspectives and perceptions of different players, such as MME, ABBEeólica, Government of Bahia, ANEEL, EPE, Investors companies of wind farms in the State, Professionals of the academies and Specialists in the area, manufacturers of equipment such as wind turbines, wind shovels, among others, as well as companies that transport these equipments to the wind farms. This work also makes an approach to the growth of this energy in Bahia, reducing the generation of energy through thermoelectric plants currently used, which are not renewable energy sources and cause environmental damage, contrary to the provisions and guidelines contained in the provisions of the Climate Convention in Paris in December 2015. This work also analyzes several aspects such as the importance of energy and transmission auctions achievements, the diverse complex logistics required to transport equipment to wind farms, the financing sources and maintenance perspectives of these contributions by BNDES, including the need for investors to seek new sources, avoiding dependence on the bank. It analyzes the regulatory framework of ANEEL and its actions in the sense of being an agent that allows clear rules to be disseminated and fulfi lled by investors through their resolutions in the sector, actions and fiscal incentives of the Bahia State government to support this productive chain and the confirmation of the need to build transmission lines so that the new wind farms of the State can be interconnected to the National Interconnected System (SIN).